استخدام اليوتوب التعليمي في البحث العلمي لدى طلبة جامعة الاغواط - وفاء زيوان; د/ الجودي بن قيط (جامعة عمار ثليجي بالاغواط, 2025)
ملخص : جاءت أهمية هذه الدراسة بعدما أصبحت شبكات التواصل الإجتماعي جزء كبير و مهم في حياة لتلقي المعرفة و تعسى الدراسة الحالية للكشف على دور موقع اليوتيوب لطلبة علوم الإعلام والإتصال ، إستخدمتالمناهج للبحوث منها النظري والتطبيقي لتحقيق أهداف الدراسة ، وتمثلت آداة جمع البيانات في الإستمارة التي وزعت على عينة الدراسة التي تكونت من 60 طالباً. كما استندت الدراسة على مدخل الإستخدامات و الإشباعات لتفسير مشكلة البحث ، وأظهرت النتائج أن دور موقع اليوتيوب في دعم طلبة الجامعية هو : مساهمة مقاطع الفيديو على اليوتيوب طلبة الجامعية في بحوثهم الجامعية ، و الحصول على معلومات عن طريق مشاهدة اليوتيوب تساعد في بحوث وإيجاد ما يبحثون عنه . و كشفت نتائج الدراسة حول عادات إستخدام اليوتيوب من طرف طلبة الجامعة أنهم يستخدمون موقع اليوتيوب بشكل مكثف ما يقارب ساعة إلى 3 ساعات يوميا و غالبا ما يكون في الفترة الليلية ، و أن أغلبية طلبة يستخدمون الهاتف الذكي كجهاز لتصفح اليوتيوب . أوضحت النتائج أن طلبة الجامعة يستخدمون اليوتيوب في المجال الدراسي بدرجة متوسطة ، كما أشارت النتائج سبب إختيار الطلبة لمشاهدة مقاطع التعليمية أثناء المراجعة راجع لأن المحتوى مقدم من طرف أساتذة و مختصين . و كشفت الدراسة أيضا أن غالبية طلبة يتابعون محتوى القنوات التعليمية والترفيهية بشكل متواصل دون القيام بأي أنشطة أخرى. الكلمات المفتاحية : شبكات التواصل الإجتماعي ، اليوتيوب ، البحث العلمي. Abstract: The importance of this study came after social networks became a large and important part of life. Each individual and using it as a way to receive knowledge. The current study aims to reveal the role of YouTube for students of media and communication sciences. Methods were used for research, including theoretical and applied, to achieve the objectives of the study. The data collection tool was represented in the form that was distributed to the study sample, which consisted of 60 students. The study was also based on the approach of uses and gratifications to explain the research problem, and the results showed that the role of YouTube in supporting university students is: contributing video clips on YouTube to university students in their university research, and obtaining information by watching YouTube that helps in researching and finding what they are looking for. The results of the study on YouTube use habits by university students revealed that they use YouTube intensively, approximately one to three hours a day, often at night, and that the majority of students use a smartphone as a device to browse YouTube. The results showed that university students use YouTube to a moderate degree in the academic field. The results also indicated the reason why students choose to watch educational clips during the review is because the content is provided by professors and specialists. The study also revealed that the majority of students follow the content of educational and entertainment channels continuously without performing any other activities Keywords: social networks, YouTube ،scientific research.
مذكرة من متطلبات نيل شهادة الماستر في علوم الاعلام و الاتصال تخصص الاتصال و علاقات عامة